A large hornet mimic clearwing moth of the genus Lamellisphecia Kallies & Arita, 2004 (Lepidoptera, Sesiidae) from Nanling, Guangdong, southern China - Arita, Yutaka; Kallies, Axel; Yata, Naoki (Zootaxa, 2019)
We here describe a new species, Lamellisphecia minwangi Arita & Kallies sp. nov., from Nanling, Guangdong, southern China. Furthermore, we provide new records of Lemellisphecia Kallies & Arita, 2004 species from south-east Asia, with L. champaensis Kallies & Arita, 2004 recorded for Laos and L. haematinea Kallies & Arita, 2004 recorded for Myanmar for the first time.